Incumplimiento de principios constitucionales por la falta de legislación en el proceso de remates del código orgánico general de procesos - Flores Ordoñez, Jenniffer Jazmin (2018)
The present research work carried out under the modality of the case study, presents as a central object of study, the process Nro. 07334-2014-0069, substantiated in the Civil Judicial Unit based in the canton Passage, through the Executive procedure, in which has shown the affectation of various constitutional principles such as legal effectiveness, legal security and effective judicial protection, as well as the effectation of the right that the creditor has to collect his credit. The stage of the judicial process where the analysis of this affectation of principles and rights is focused, is in the execution, specifically in the process of auctions of seized assets established by the General Organic Code of Processes. Because the problem of the central object of study, is the impossibility of collecting your credit, because despite the indications to auction that determines the law, which were met, has not been achieved the sale of it.